The Translation Analysis of Nadin Amizah’s song entitled Bertaut in Indonesia to English - Nabilah, Layalia (Universitas Terbuka, 2025)
Translating song lyrics involves unique challenges, particularly in preserving the nuances of meaning, emotional depth, and music while adapting the text for a new audience. This study aims to determine the kinds of translation methods used in Emma Heester's rendition of Nadin Amizah's song ‘Bertaut’. This research used a descriptive-qualitative approach. The investigator analyzed the data using a variety of translation hypotheses advocated by Peter Newmark. 18 data points are included in Emma Heester's translation of Nadin Amizah's song ‘Bertaut’ per the study's conclusions. Out of the 18 data, four types of translation were used: free translation (6 data), literal translation (5 data), communicative translation (4 data) and semantic translation (3 data). For the most part, the lyrics are translated using free translation. This is because the translation altered the content, added details, and adjusted subtleties in the original language to produce ideal syllables and tone for target language listeners.